Caracterización geomecánica de la galería principal de la Mina Numinec - Fernández Macas., Andy Alexander (2022)
One of the purposes of geomechanical characterization in underground mining is to maintain safety in the galleries by detecting in time potential failures that could cause instability problems. In the gallery under study, the main potential failure that affects the stability of the excavation and that could cause damage to personnel and equipment is the detachment or fall of rocks either from the roof or gables of the gallery. The objective of this research is to characterize geomechanically the main gallery of the Numinec mine, with a study length of 656 meters, for the recommendation of support measures in order to avoid or reduce accidents due to rock falls. In order to meet the proposed objective, a methodology based on the application of the geomechanical classifications of Bieniawski, Barton, Lien and Luden and the Geological Resistance Index was used, in addition to the kinematic analysis using the Dips software and the support simulation using the Unwedge software. The main gallery was divided into 23 study sections where the aforementioned methodology was applied, the results obtained were the evaluation of the geomechanical parameters of each classification and its corresponding massif quality, together with stereograms that allowed the identification of the main families of diaclases and also improved support models were developed to define the most adaptable type of support. The most influential geomechanical parameters when characterizing the gallery are: rock strength, water infiltration and number of joints. The quality of the rock mass that predominates according to the RMR classification is medium quality, according to Barton's Q classification, poor quality prevails, and according to the GSI classification, medium and poor quality dominates. The stereograms identified 22 sites with suitable conditions for wedge formation. The support modeling defined that the cemented helical bolt, reinforced in some sections with electrowelded mesh, is the most suitable support measure for the study area. Key words: geomechanical characterization, mining, underground mining, rock mass, support.